KEPUASAN PELANGGAN MEMEDIASI PENGARUH KUALITAS PROSES, KUALITAS INFRASTRUKTUR, DAN KUALITAS INTERAKSI TERHADAP LOYALITAS PELANGGAN - Bidari Andria Devi; Wisnu Untoro (MIX: JURNAL ILMIAH MANAJEMEN, 2019)
This research was conducted for analyze the influence of process quality , infrastructure quality and interaction quality on customer loyalty with customer satisfaction as mediating variable. This study employed quantitative method, and questionnaire for collecting data. The sampling technique employed was accidental sampling one. The sample of research consisted of 170 respondents in inpatient units of type-D hospitals in Sukoharjo divided into PKU Muhammadiyah and Nirmala Suri Hospitals. The analysis method employed in this research was Structural Equation Modeling (SEM) with SmartPLS 2.0 program help. Validity and reliability tests were analyzed using outer model, while inner model was used to test hypotheses. Result of research showed that process quality ,infrastructure quality, and interaction quality affected customer loyalty positively and significantly and customer satisfaction , customer satisfaction mediates relationship  between process quality,infrastructure quality,and interaction quality to customer loyalty . So that the better the process  quality, infrastructure quality,and interaction   quality  the higher is the customer satisfaction and customer lotalty  of type-D hospitals in Sukoharjo